2014
DOI: 10.5862/mce.49.11
|View full text |Cite
|
Sign up to set email alerts
|

Tubular composite columns in a non-symmetrical fire

Abstract: A considerable number of studies have been conducted worldwide on fires that act on all four sides of a column (symmetrical fire). These cases are used for the validation of the analysis models developed in this study. In real buildings the columns are often embedded.If the fire does not act similarly on all surfaces of the column (non-symmetrical fire), it is extremely difficult to predict how the column will behave. The key research questions are: Is resistance stronger in non-symmetrical than in symmetrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The behaviour of steel columns in non-symmetrical fire has been studied by [13] and [14], and concrete filled steel tube columns in non-symmetrical fire were researched by [15][16][17][18]. Additionally, Schaumann et al [19] have studied the temperature behaviour of a steel beam, which is protected by intumescent coating, but supports a trapezoidal steel sheet, which partially inhibits the coatings expansion.…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of steel columns in non-symmetrical fire has been studied by [13] and [14], and concrete filled steel tube columns in non-symmetrical fire were researched by [15][16][17][18]. Additionally, Schaumann et al [19] have studied the temperature behaviour of a steel beam, which is protected by intumescent coating, but supports a trapezoidal steel sheet, which partially inhibits the coatings expansion.…”
Section: Introductionmentioning
confidence: 99%
“…According to Article 76 of the Federal Law of July 22, 2008 N 123-FL, the arrival time of the first fire brigade to the place of call in urban areas should not exceed 10 minutes. The constantly increasing number of new residential complexes with low infrastructure in the city and its districts, numerous large traffic jams, temporary road repairs and weather conditions reduce the radii of service of fire departments, and for this reason there is a need to identify unsafe areas to which fire brigade in case of emergency will not be able to arrive within a certain time [8][9][10][11][12]. Three main regulatory documents, that control value of time, distance and location of fire department, make current situation more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…The non-symmetric heating of tubular columns filled with concrete was experimentally tested in Yang et al [4][5][6] and numerically in Heinisuo et al 7 The research stud-ies showed that the number of sides on which fire acts has a major influence on the heat distribution and fire resistance. With an increasing number of sides exposed to fire, the fire resistance in the square hollow section (SHS) concrete-filled columns decreases along with the ambient conditions.…”
Section: Introductionmentioning
confidence: 99%